(untitled) (International Journal of Engineering and Computer Science, 2017)
Agriculture sector is a contributor of GDP and foreign exchange for a nation. Agriculture sector generates labor, capital and fulfill domestic demand to support growth in other sectors as well. Agriculture sector plays a key role in ensuring national food security. Access to the agricultural marketing information is an essential factor in promoting competitive markets, globalization, efficient marketing, market liberalization and improving development of agricultural sector. Majorities of the stakeholders of the said sector are deprived of agricultural marketing information. The stakeholders of agriculture sector of Saudi Arabia are in need of Agricultural Marketing Information System (AMIS). In this paper we proposed the AMIS for the Kingdom of Saudi Arabia. In summary, the said system is aimed at providing agricultural marketing information to all the stakeholders of Saudi agriculture sector